2017
DOI: 10.1016/j.ekir.2017.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Novel Therapies for Acute Kidney Injury

Abstract: Acute kidney injury (AKI) is a common disease with a complex pathophysiology. The old paradigm of identifying renal injury based on location—prerenal, intrarenal, and postrenal—is now being supplanted with a new paradigm based on observable kidney injury patterns. The pathophysiology of AKI on a molecular and microanatomical level includes inflammation, immune dysregulation, oxidative injury, and impaired microcirculation. Treatment has traditionally been supportive, including the avoidance of nephrotoxins, ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 150 publications
0
47
0
Order By: Relevance
“…The top disease network in CKD was attributed to cardiovascular disease (Figure A). In AKI, free radical scavenging was the top (dys)functional network (Figure B) confirming potential use of oxygen‐free radical scavengers in the treatment of AKI . Therefore, overall, the data extracted from these proteome‐based studies in preclinical kidney disease models appear to have validity when comparing to the currently known disease‐involved biological mechanisms.…”
Section: Pathway Analysis Of Proteome Data Of Preclinical Kidney Disementioning
confidence: 70%
“…The top disease network in CKD was attributed to cardiovascular disease (Figure A). In AKI, free radical scavenging was the top (dys)functional network (Figure B) confirming potential use of oxygen‐free radical scavengers in the treatment of AKI . Therefore, overall, the data extracted from these proteome‐based studies in preclinical kidney disease models appear to have validity when comparing to the currently known disease‐involved biological mechanisms.…”
Section: Pathway Analysis Of Proteome Data Of Preclinical Kidney Disementioning
confidence: 70%
“…63 A single-centre study in 200 adults who underwent valvular heart surgery reported a significantly lower AKI incidence in patients treated with dexmedetomidine starting with anaesthesia induction and continued until 24 hours after surgery vs placebo controls (14% vs 33%). 3 Currently, reverse translational approaches are taken to better match animal models of renal IR to clinical situations that cause AKI. 65 Together, available data on the efficacy of sympatholytic drugs added peri-operatively to the patients' medications in clinical scenarios where renal ischaemia and sympathetic activation likely contribute to AKI are ambiguous.…”
Section: Of 10mentioning
confidence: 99%
“…A single brief ischaemia period as induced by clamping the renal pedicle or the renal artery in laboratory animals may not adequately model most clinical conditions that lead to AKI were fluid resuscitation, agents with potent anti-inflammatory actions and vasopressors such as noradrenaline are important therapeutic measures. 3 Currently, reverse translational approaches are taken to better match animal models of renal IR to clinical situations that cause AKI. [66][67][68] Their use in studies on the role of sympathetic activation may improve translatability of experimental data.…”
Section: Clinical Akimentioning
confidence: 99%
See 2 more Smart Citations